Carrier aggregation‐based dynamic spectrum access framework for LTE‐A primary operators. Issue 13 (1st September 2016) - AbdelFadeel, Khaled Qorany; Khattab, Ahmed; Elsayed, Khaled; Digham, Fadel
Abstract : In this study, the authors tackle the dynamic spectrum access (DSA) problem for primary operators (POs) for long‐term evolution‐advanced (LTE‐A) systems. They propose an auction‐based DSA framework that exploits the capabilities of carrier aggregation to efficiently utilise the under‐utilised spectrum which varies with time and space. Their proposed dynamic access framework defines the LTE‐A resource allocation problem as a bounded knapsack auction (BKA). They solve such a BKA by converting it to a 0–1 knapsack problem that is solved using dynamic programming. Unlike prior work, they are the first to introduce an accurate model for estimating the bandwidth required to satisfy the traffic demands of an LTE‐A operator's subscribers for a projected demand model. Using extensive simulations of such a realistic network model, the results of their framework show more than 20% reduction in the required spectrum and up to 80% reduction in the average under‐utilised spectrum compared with traditional static spectrum access widely adopted by spectrum regulation authorities. The reduction in the average under‐utilised spectrum becomes 93.3% with 250% higher revenue compared with existing dynamic allocation strategies that are directly formulated as 0–1 knapsack auctions.